2021
DOI: 10.1007/s41999-021-00488-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient self-reported functioning by pain severity and usual analgesic treatment among older adults with osteoarthritis: analysis of the 2017 Spanish National Health Survey

Abstract: BackgroundOsteoarthritis (OA) pain is among the leading causes of disability and social isolation worldwide. Since prevalence is high, particularly in adults aged 65 or older, it represents a signi cant burden for society and national health systems. The objective of this study was to determine whether patient self-reported functioning in key domains of daily living differs by pain severity and analgesic treatment among older OA patients in Spain. MethodsThe Spanish National Health Survey (ENSE), a large, nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Osteoarthritis is the most common form of arthritis 1 and is characterized by pain, which can lead to limitations in activities of daily living and reduced quality of life 2 , 3 . Indeed, cross-sectional studies report a significant association between pain severity and activities of daily living in older adults with osteoarthritis 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis is the most common form of arthritis 1 and is characterized by pain, which can lead to limitations in activities of daily living and reduced quality of life 2 , 3 . Indeed, cross-sectional studies report a significant association between pain severity and activities of daily living in older adults with osteoarthritis 4 , 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Those with increased pain intensity were likelier to report a functional limitation [ 33 ]. In addition, a cross-survey of the Spanish National Health Survey found that pain severity was the most crucial indicator of PF decline and caregiving demand in older adults with OA in Spain [ 34 ]. Furthermore, a double-blind randomized controlled trial assessed pain management by administering opioid analgesics to individuals with chronic back pain and discovered that acute opioid analgesic administration enhanced lifting capacity by 15% to 48%.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, as individuals experience greater difficulty in executing basic tasks, their dependence makes them less motivated to interact in society and even with their own family, resulting in social isolation. 20 Older adults who are completely dependent require care that their families are often unable to provide due to work…”
Section: Discussionmentioning
confidence: 99%